Специфіка використання маркетингових комунікацій у ресторанному бізнесі - Вардеванян, Вардан; Vardevanyan, Vardan; Vardevanian, Vardan (Черкаський державний технологічний університет, 2017)
У статті здійснений аналіз особливостей використання системи маркетингових комунікацій у діяльності підприємств ресторанного бізнесу. Визначено чинники, що впливають на вибір складу інструментів маркетингових комунікацій у діяльності підприємства. Сформовано принципи здійснення такого відбору. A problem of positioning in the market has always existed for food establishments. The nature of the market and the essence of the institution are determining factors in this situation. The restaurant is not only and not just a place to eat. This is a place for ritual events (celebration of a determinant event in the circle of friends, declaration of love, business meeting, corporate event, funeral, etc.). Therefore, in addition to menus and prices, important components in competing restaurants are: the location and equipping of premises, target audience, related services, the way to deliver information to the target audience. It makes catering establishments to use the system of marketing communications in a different way. The advertising is the main tool for informing consumers. But it should be noted that not all promotional tools you need to use a single catering establishment. It is not always useful. The selection of advertising tools must be implemented carefully and thoroughly. The article examines the factors that affect this choice of components of marketing communications. Among the factors we have identified the following: - belonging to a certain type of catering industry. The higher is the grade of the restaurant, the richer must be consumer, on whom communication program of the institution is oriented. This means that such institutions must have a unique set of channels for disseminating information to their clients; - the availability of a certain conception of the institution. The concept of a restaurant or bar is a clear vision of typical customer, understanding his needs and preferences. This knowledge determines the decision on the nature of the establishment, its field of expertise, interior and exterior of premises, menus, entertainment programs, the mode of operation and staff clothing, and many other things – this should meet the purpose, concept of operation of the establishment. Advertising of a restaurant or bar must also be designed in the framework of the developed style. You also need to carry out a careful selection of channels of advertising communication; - the location of the establishment. This factor greatly influences on the choice of establishment type and the concept of its work and promotion. If the establishment is in the center of the intersection of routes of pedestrian active movement, it is necessary to provide fast and quality service. As soon as there is a barrier, such as the second floor of the premises, then this goal will be harder to achieve. Obviously, you need to move to another level of the work with the target audience. And a significant amount of work to be done will be passed on advertising communication and other tools of marketing communications. In addition, it will also identify the use of the tools of marketing communications. We have determined the principles which are the following: to clearly understand the concept of work and concept of advertising campaign; to know the portrait of the audience, and to navigate the demands and motives of their customers; to use only those communication channels that are in active use by the target audience of a restaurant or bar; to clearly articulate goals of the establishment.
SPECIFIC USE OF MARKETING COMMUNICATIONS IN RESTAURANT BUSINESS
Keywords: маркетингові комунікації; реклама; рекламна кампанія; ресторан; marketing communications; advertising; advertising campaign; restaurant